(untitled) (Fiep Bulletin - online, 2012)
The present study aims to verify the existence of a connection between obesity and indicators of physical fitness related to the health of schoolchildren in the town of Santa Cruz do Sul. The cross-sectional study was of descriptive exploratory nature, involving 98 schoolchildren, 51 male and 47 female, using BMI as a collection tool for body composition, and tests of flexibility, strength/endurance and abdominal cardio respiratory testing for evaluating health-related fitness. For data analysis, we used the SPSS v. 18.0, through the Student t test and Pearson correlation. The results of this survey indicate that, although no correlation between BMI and health-related fitness was found, the averages for the abdominal and VO2max tests were higher for the nonobese group. Therefore, we concluded that obese schoolchildren had a lower performance in the tests of physical fitness related to health compared to nonobese schoolchildren.